Prevention of COVID-19 during youth ice hockey - Chilibeck, P. D. (Applied Physiology, Nutrition, and Metabolism, 2023)
Ice hockey players are susceptible to COVID-19 because of close contact and poor arena ventilation. Preventive strategies include reducing arena crowding, practice strategies that reduce clustering of players, at-home rapid tests, symptom screening, and face mask or vaccine recommendations for spectators, coaches, and players. Face masks have little effect on physiological responses or performance and reduce COVID-19 transmission, but shifts should be shortened later in periods to reduce perceived exertion and players should be encouraged to assume a classic "hockey stance" when puck handling to improve peripheral vision. These strategies are important to prevent cancelation of practices or games, which have important physical and psychological benefits.